2019
DOI: 10.1002/jcp.28979
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of microRNA‐103 attenuates inflammation and endoplasmic reticulum stress in atherosclerosis through disrupting the PTEN‐mediated MAPK signaling

Abstract: Atherosclerosis (AS), a chronic disorder of large arteries, is the underlying pathological process of heart disease and stroke. Former researchers have found that microRNAs (miRs) are involved in the several key processes of AS. Apolipoprotein E knockout (ApoE −/− ) mice fed a high-fat-diet (HFD) to establish AS model. The expression of miR-103 was characterized in the mice model. The effects of miR-103 on inflammation and endoplasmic reticulum stress (ERS) were analyzed when the expression of miR-103 was inhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 50 publications
(52 reference statements)
0
29
0
Order By: Relevance
“…However, PTEN has been reported to be inhibited by many microRNA (miRNA) and performed neuroprotective effect against ischemic stroke in experimental models. miR-103 can target PTEN and downregulate its expression, which depletion restrains the progression of atherosclerosis through blocking PTEN-mediated MAPK signaling [ 11 ]. Another data demonstrates that miR-130a prevented cerebral ischemia/reperfusion damage against ischemic stroke by mediating the PTEN/PI3K/AKT pathway [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, PTEN has been reported to be inhibited by many microRNA (miRNA) and performed neuroprotective effect against ischemic stroke in experimental models. miR-103 can target PTEN and downregulate its expression, which depletion restrains the progression of atherosclerosis through blocking PTEN-mediated MAPK signaling [ 11 ]. Another data demonstrates that miR-130a prevented cerebral ischemia/reperfusion damage against ischemic stroke by mediating the PTEN/PI3K/AKT pathway [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contributions from miRNAs to inflammatory processes have been demonstrated for a multitude of diseases (123), including rheumatoid arthritis (126), psoriasis (124), asthma (78), ulcerative colitis (147), systemic lupus erythematosus (133), different forms of glomerulonephritis (93), and also atherosclerosis (51,127).…”
Section: Neutrophil Leukocytesmentioning
confidence: 99%
“…Color images are available online. model (51). Depletion of miR-103 was shown to counteract atherosclerosis through blocking phosphatase and tensin homolog (PTEN)-mediated mitogen-activated protein kinase (MAPK) signaling (51).…”
Section: Neutrophil Leukocytesmentioning
confidence: 99%
“…Alternatively, reduced expression of miR-103 limits the occurrence of AS by preventing miR-103-induced lncwdr59 inhibition, thereby protecting endothelial cells from endothelial damage and reducing the targeted inhibition of Kruppel-like factor 4 (kfl4) [20]. Other studies have found that low miR-103 expression results in enhanced expression of the downstream target gene, phosphatase, and tensin homolog deleted on chromosome 10 (PTEN), which inhibits the p38 mitogen-activated protein kinase (MAPK) signaling pathway and reduces the inflammatory response and ER stress response in endothelial cells exposed to oxidized low-density lipoprotein (ox-LDL) [21]. Moreover, miR-103 knockout reduces the necrosis of H9C2 cells treated with H 2 O 2 , by regulating the downstream target gene Fas-associating protein with death domain (FADD) and preventing the formation of the ripk1/ripk3 complex [22].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, low miR-103 expression reduces the formation of the ripk1/ripk3 complex by activating FADD and effectively reducing the occurrence of myocardial necrosis induced by oxidative stress [22]. Moreover, in hyperlipidemia, miR-103 promotes endothelial cell regeneration, reduces or suppresses PTEN/MAPK signaling by promoting the expression of lncwdr59, and attenuates cell damage caused by endoplasmic reticulum stress [20,21]. However, other studies suggest that low miR-103 expression may cause cell damage.…”
mentioning
confidence: 99%